CDSD-296, high-resolution carbon dioxide spectroscopic databank: An update. (May 2019) - Tashkun, S.A.; Perevalov, V.I.; Gamache, R.R.; Lamouroux, J.
Highlights: CDSD-296 is aimed at atmospheric applications. CDSD-296 contains data of all 12 stable CO2 isotopologues. CDSD-296 is based on global fits of measured line positions and intensities. CDSD-296 broadening and shifting data are based on the Gamache and Hartmann model. CDSD-296 contains calculated line parameters for the 345 – 14, 075 cm −1 spectral range. Abstract: In 2015 we published an atmospheric version, CDSD-296, of the carbon dioxide spectroscopic databank (CDSD) [Tashkun et al., JQSRT 152 (2015) 45–73]. Since that time many new experimental data have been published. Some CDSD data deficiencies have also been found. The purpose of the present work is to present a corrected and extended version of the databank. In particular, it includes more realistic uncertainties of the line positions and intensities. The databank contains the calculated line parameters (positions, intensities, air- and self-broadened half-widths and their coefficients of temperature dependence, as well as air- and self- pressure-induced shifts) of the twelve stable isotopic species of CO2 . The reference temperature is 296 K, and the intensity cutoff is 10 − 30 cm − 1 /(molecule cm − 2 ). More than 530, 000 lines covering the 345–14, 076 cm −1 spectral range are included in the databank. Comparisons of the new version of the CDSD with UCL, AMES and HITRAN2016 line lists are also given.